Supplemental Foods Affect Energetic Reserves, Survival, and Spring Reproduction in Overwintering Adult Hippodamia convergens (Coleoptera: Coccinellidae). Issue 1 (21st November 2019) - Mercer, Nathan H; Teets, Nicholas M; Bessin, Ricardo T; Obrycki, John J
Abstract: For insects that overwinter as adults, winter food resources may affect subsequent spring reproduction and abundance. We tested if provision of food supplements to overwintering adult Hippodamia convergens (Guerin) increased energy reserves, winter survival, and spring reproduction. During 2015–2016, H. convergens adults were placed in field cages in December; adults in each cage received water, Acyrthosiphon pisum (Harris) (Hemiptera: Aphididae), Ephestia kuehniella (Zeller) (Lepidoptera: Pyralidae) eggs, bee pollen, wheast protein, sugar, honey, or no food (control). In 2016–2017, treatments were reduced to sugar, bee pollen, A. pisum with E. kuehniella eggs, and no food (control). Adults were sampled to quantify weight, lipid, carbohydrate, and protein content. In 2015–2016, A. pisum and E. kuehniella eggs increased adult weight and protein content, but adult carbohydrate content was reduced by A. pisum and wheast protein treatments. Adults receiving honey and sugar supplementation had higher lipid and carbohydrate content relative to controls. The number of live individuals at the end of the experiment in March 2016 did not differ among treatments. In 2016–2017, winter prey supplements had the greatest effect on protein content, weight, and number of live adults recovered, whereas sugar supplementation increased lipid and carbohydrate content, and number of live adults recovered. Spring reproduction of surviving pairs was evaluated among treatments in March 2017. Prey supplementation in 2016–2017 increased the number of eggs laid and decreased preoviposition period, and food treatment did not affect fertility. Our results indicate that prey and sugar resources improve the overwintering success and spring reproduction of H. convergens .